Algumas representações sociais sobre interdisciplinaridade para professores do CIEP 098 - Sardinha, Tânia Fonseca da Rocha (2013)
This thesis proposes further study about the social representations of interdisciplinarity for public school teachers, under the theoretical framework of Sége Moscovici. While educational phenomenon, interdisciplinarity is still contentious in the classroom. We appealed then to the qualitative study based on the dimensions Novikoff. Initially surveys were conducted to delineate the State of Knowledge, heading for the field research with teachers from State School Hilda Carmo Siqueira - CIEP 098, in the municipality of Duque de Caxias, in the state of Rio de Janeiro. Data collection was by performing a projective technique with free recall of words, based on Jorge Visca. To sustain the present study sought to considerations about the emptying function of a teacher articulating the continuing education of teachers and the role of interdisciplinarity with theoretical support sustained in philosophy and education. The study has enabled us to discuss interdisciplinarity as a polysemic concept and a social representation that is shaping up in the joint effort, but without provoking attitude. A junction of disciplines, but not a change in attitude.